A new species of the deep-sea shrimp genus Spongicoloides (Decapoda: Spongicolidae) from the South China Sea - Zhao, Yu; Xu, Ting; Yang, Weidi; Qiu, Jian-Wen (Zootaxa, 2021)
Spongicoloides zhoui sp. nov. (Crustacea: Decapoda: Spongicolidae), a species of deep-sea hexactinellid sponge-associated shrimp, is described based on specimens collected from the Zhenbei Seamount in the South China Sea. The new species is morphologically most similar to the Western Pacific congeneric species Spongicoloides iheyaensis Saito, Tsuchida & Yamamoto, 2006 in that the ischium of the third pereiopod is unarmed and the fixed finger of the third pereiopod is armed with small teeth on the distoventral margin. However, S. zhoui sp. nov. can be distinguished from S. iheyaensis in that its female antennal basicerite has three large spines on the distolateral margin. Molecular analyses based on nuclear histone H3, and mitochondrial cytochrome c oxidase subunit I (COI), 12S ribosomal RNA (rRNA), and 16S rRNA gene fragments confirmed the placement of S. zhoui sp. nov. within a clade of Spongicoloides/Spongiocaris species, and their sequence divergences were large enough to justify the recognition of this new species.